The Effect of Male Age on the Quality of Bali Cattle Fresh Semen - N. Nirwana; S. Suparman (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
This research was conducted by conducting experiments in UPTD laboratory of Livestock and Livestock Feeding Agricultural Service of Sulawesi Barat Province. The purpose of this research is to compare the age of males during March to April 2013. The results of this research are expected to be used as a guideline for the use of Bali Cattle research as a semen producer based on the age of livestock that can be used as one of the criteria in the selection of prospective semen producing males. The research material is fresh semen of Bali Cattle with requirement of 70% individual motility. The research method used is observation method by observing the fresh semen quality of Bali Cattle research which has been classified into 3 groups based on age 3, 5, and 6 years. The data analysis used is the analysis of the variety and the design is Completely Randomized Design. The results showed that the quality of fresh semen in the three age groups (3, 5, and 6 years) where volume: 5.2 ± 1.2; 6.4 ± 1.1; And 6.4 ± 0.8 ml, color: milk, white, pH: 6,4 ± 0,1; 6.4 ± 0.1; And 6.3 ± 0.1, consistency: concentrated; Medium; Concentrated and concentrated, concentrations: 1909.6 ± 418.8; 1223.3 ± 220.8; And 1790.8 ± 240.5 million / ml, and 92.5 ± 2.9%, abnormality: 4.4 ± 1.2; 4.3 ± 1.2; And 3.3 ± 1.0%. The conclusions of this research indicate that the age of males gives a significant effect on the fresh semen volume, fresh semen concentration, gives a very significant effect on fresh semen concentration and does not have a significant effect on fresh semen sperm abnormalities. And a male of Bali Cattle age 3-6 years old in UPTD Livestock Feeding and Animal Feed Agricultural Service of Sulawesi Province has good semen quality for Artificial Insemination.